New campus-North Gym-0036 (1953)
Home Of The Fresno State College Basketball Team and the men's physical education department is the $931,700 gymnasium. The structure, which was occupied in the fall of 1953, boasts a swimming pool-easily openped to an enclosed patio by the movement of a glass wall-and seating accommodations for approximately 2,500 persons.